Decoding 'effectiveness' in climate change adaptation - Insights from research - Njuguna, Lucy (2023)
Article 7.1 of the Paris Agreement articulates a global goal on adaptation, which aims to ensure an ‘adequate adaptation response’ complementary to the objective of limiting global temperature rise to "well below 2°C and to 1.5°C”. The Paris Agreement further requires countries to regularly review the ‘adequacy’ and ‘effectiveness’ of adaptation and the support provided for adaptation. However, conceptual and methodological hurdles persist in defining such a goal and varying evidence on what effective adaptation is and how it can be facilitated. Moreover, as adaptation is highly context-specific, a universal definition of what ‘effective adaptation’ is particularly challenging and more so, how to operationalize it. This presentation highlights a researcher’s perspective on how to measure adaptation effectiveness by highlighting the value of grounding measurements in robust conceptual frameworks and co-producing tools with relevant stakeholders to capture diverse perspectives and adaptation priorities. It also showcases practical application of these principles in the development of tools for tracking adaptation in the agriculture sectors in Africa. The presentation was made at a side event at COP28 on December 5, 2023.